Solids flow pattern in cold flow mockup of fluidized bed gasifier. (31st December 2019) - Roy, Sangram; Pant, Harish Jagat; Roy, Shantanu
Highlights: Solid flow pattern of coal and ash mixtures determined through Radioactive Particle Tracking (RPT) in fluidized bed. For the present operating conditions, a largely slugging solid flow pattern was observed across the bed. Analysis of mean and velocity distributions indicate non-uniformity in distributions across axial planes is presented. Abstract: We report solids flow pattern in a laboratory-scale fluidized bed of coal and ash mixtures. Suitable tracers were designed and deployed to determine the solids flow path of a typical particle through Radioactive Particle Tracking (RPT). Experiments were conducted in a cylindrical bed of 0.1 m in i.d. with two inventory compositions, namely, 70% Coal + 30% Bottom Ash (Composition I) and 20% Coal + 80% Bottom Ash (Composition II). Comparative analysis of RPT measurements yielded overall bed behavior, which was quantified in terms of time-averaged mean velocity, solids flux, RMS velocity, and kinetic energy per unit volume of the coal – bottom ash mixture. The mean axial velocity and solids flux profile indicated the influence of strong slugs on the solids flow patterns.